PEMBERDAYAAN MASYARAKAT DALAM PENINGKATAN IMTAQ DAN IPTEK DI KELURAHAN ULUJAMI - Peni Maulidia; Farhan Arif Al Farisi; Much Hasan Darojat (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The condition of the metropolitan community which tends to be busy and hedonistic causes the emergence of social phenomena in the community, one of which occurs among the people in Ulujami Village. The social phenomenon that occurs causes low public concern for participation in social, religious activities and awareness of the importance of mastering technology for owners of micro, small and medium enterprises (MSMEs). Based on these problems, Darunnajah University students took the initiative to create a community service program by carrying out community empowerment activities to improve religious awareness, science and technology also the integration of the two in Ulujami Village, South Jakarta. Because by combining these aspects in life, it can establish a rabbani civilized community. Meanwhile, the implementation of technology is carried out for MSME owners to be able to develop their business through marketing with social media and online.